Model Optimasi Jaringan Rantai Pasok Pada Sistem Informasi Harga Karet Rakyat Berbasis Web - Irvai, Muhammad; Herdiansyah, Muhammad Izman (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The supply chain problems have traditionally resulted in inefficient distribution of the people's rubber production. The research scope is in Musi Rawas district. The purpose of this research is to optimize the people's rubber supply chain from each supply chain channel using an information system. The method of analysis used in this research is Linear Programming (LP). Conveyance capacity and labor hours serve as constraint functions, while the objective function is to maximize distribution profits from each rubber supply chain channel. From the results of testing the Quantitative Management (QM) application with a sample of farmers 1, village collectors 1 and sub-district 1 collectors in the first channel, a solution of type A products is obtained, which is 625 and a profit of X1 = 8218, then multiplied into a profit of Rp. 5,136,250. From the results of testing the Quantitative Management (QM) application with a sample of farmers and village / sub-district collectors 1 in the second channel, it was found that the product type A solution was 500 and the profit X1 = 7923, the profit was Rp. 3,961,500. From the results of testing the Quantitative Management (QM) application with a sample of farmers and UPPB 1 in the third channel, the solution for type B products is 562.5 and the profit X2 = 9897, the profit is Rp. 5,567,063. So from the results of the analysis using the QM application, the maximum benefit from the people's rubber supply chain in Musi Rawas district is in the third channel